Of Pearls and Coral: Jurisography and Ego History - John Docker (Law Text Culture, 2016)
In this talk I’d like to create a conversation between what Ann Genovese and Shaun McVeigh (2015) felicitously call ‘jurisography’, which is, we might say, just beginning its intellectual journey as a concept of great fertility and possibility, and what the French historiographer Pierre Nora (2001) refers to as ego-histoire, or ego history, which is now becoming an international intellectual movement. As will become clear, ego history is not simply to be identified with autobiography. I also do not equate ego history with jurisography. I wish to suggest there might be resonances between jurisography and ego history that we might think about.